2015
DOI: 10.1002/ar.23160
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microstructure of the Stereospondyl Lydekkerina Huxleyi Reveals Adaptive Strategies to the Harsh Post Permian‐Extinction Environment

Abstract: The small-bodied stereospondyl Lydekkerina huxleyi, dominated the amphibian fauna of the South African Lower Triassic. Even though the anatomy of this amphibian has been well described, its growth strategies and lifestyle habits have remained controversial. Previous studies attributed the relative uniformity in skull sizes to a predominance of subadult and adult specimens recovered in the fossil record. Anatomical and taphonomic data suggested that the relatively small body-size of this genus, as compared to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…Also from South Africa, five Lystrosaurus specimens from the lower Lystrosaurus AZ have δ 18 O p values similar to those of the co-existing semi-aquatic stereospondyl Lydekkerina (Schoch, 2008; Canoville and Chinsamy, 2015). In addition, an indeterminate lystrosaurid from the Induan Jiucaiyuan Formation of the Xinjiang Province has a δ 18 O p value similar (with a difference of −0.1 ± 0.6‰; Figure 2B) to that of the proterosuchid ‘ Chasmatosaurus ’ yuani , a basal archosauriform considered terrestrial and possessing an intermediate thermometabolsim based on a palaeohistological study (Botha-Brink and Smith, 2011).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Also from South Africa, five Lystrosaurus specimens from the lower Lystrosaurus AZ have δ 18 O p values similar to those of the co-existing semi-aquatic stereospondyl Lydekkerina (Schoch, 2008; Canoville and Chinsamy, 2015). In addition, an indeterminate lystrosaurid from the Induan Jiucaiyuan Formation of the Xinjiang Province has a δ 18 O p value similar (with a difference of −0.1 ± 0.6‰; Figure 2B) to that of the proterosuchid ‘ Chasmatosaurus ’ yuani , a basal archosauriform considered terrestrial and possessing an intermediate thermometabolsim based on a palaeohistological study (Botha-Brink and Smith, 2011).…”
Section: Resultsmentioning
confidence: 85%
“…A study dedicated to Rhinesuchus palaeohistology concluded that it had a fully aquatic lifestyle (McHugh, 2014), whereas Lydekkerina , a basal stereospondyl, was amphibious with a tendency to be terrestrial (Canoville and Chinsamy, 2015). …”
Section: Theoretical Curves Constructionmentioning
confidence: 99%
“…Histological analyses of the postcranial skeleton of Temnospondyli are usually based on long bones, vertebrae or dermal bones (de Buffrénil et al 2016;Canoville and Chinsamy 2015;Damiani 2000;Gee et al 2017;Konietzko-Meier and Klein 2013;Konietzko-Meier and Sander 2013;Konietzko-Meier and Schmitt 2013;Konietzko-Meier et al 2012McHugh 2014;Mukherjee et al 2010;Ray et al 2009;de Ricqlès 1979;Sanchez and Schoch 2013;Sanchez et al 2010a, b;Steyer et al 2004;Witzmann 2009;Witzmann and Soler-Gijon 2010). However, only two histological studies are applied on humeri (Konietzko-Meier and Sander 2013; Mukherjee et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar developmental plasticity is thus to be expected in temnospondyls and indeed is documented within the clade (e.g., Sanchez and Schoch, 2013;Schoch, 2014;Canoville and Chinsamy, 2015). We believe that this conservative approach is appropriate, given the relatively poor knowledge of early stages of ontogeny in trematopids.…”
Section: Taxonomic Affinitiesmentioning
confidence: 55%